The physicochemical characteristic of biodegradable methylcellulose film reinforced with chicken eggshells. (2018) - Siriprom, W.; Sangwaranatee, N.; Hidayat, R.; Kongsriprapan, S.; Teanchai, K.; Chamchoi, N.
Abstract: The present study aims to investigate the structural, chemical and morphology properties of methylcellulose film with reinforced by chicken eggshells. The physical properties were determined with X-Ray Diffraction (XRD) and the Scanning Electron microscopies (SEM) while the chemical properties can be discussed by Fourier transform infrared spectroscopy (FTIR). The XRD pattern indicated that, the methylcellulose film with reinforced by chicken eggshells have been amorphous-crystalline structure. On the other hand, the SEM micrographs exhibited the granule of chicken eggshells powder distribution along the surface. For the results of Chemical properties FTIR spectra can be used confirm the chicken eggshells powder presence in the methylcellulose film. For mechanical properties, the effects of chicken eggshells on the methylcellulose film investigated by tensile testing.